An oldest‐old non‐small cell lung cancer patient with abscopal effect in a single lesion. Issue 15 (27th June 2022) - Sakaguchi, Tadashi; Ito, Kentaro; Fujiwara, Kentaro; Nishii, Yoichi; Ochiai, Satoru; Nomoto, Yoshihito; Hataji, Osamu
Abstract: The abscopal effect without concomitant immunotherapy is a rare event, including among cases of lung cancer. Furthermore, the occurrence of limited abscopal effect for only a single lesion in the metastatic organ consistent with the irradiated organ would be an even more rare event. A 94‐year‐old man was diagnosed with advanced lung cancer with osteolytic bone metastases in his right iliac bone, and the right side of his axial vertebrae. After palliative radiation therapy to the right iliac lesion for pain relief without other anticancer therapy, the axial vertebral osteolytic lesion disappeared despite no reduction in the other lesions. This case furthers our understanding of the pathogenesis of the abscopal effect. Abstract : An oldest‐old non‐small cell lung cancer patient with bone metastases in his iliac bone and axial vertebrae. After palliative radiation therapy to his iliac lesion for pain relief, the axial vertebral osteolytic lesion disappeared despite no reduction of the other lesions. The abscopal effect is a rare event; furthermore, an occurrence of limited abscopal effect for only a single lesion in the metastatic organ consistent with the irradiated organ would be an even more rare event.